2017
DOI: 10.1242/bio.029090
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of H3K27me3, H3K9me3, and H3K4me3 along autophagy-related genes highly expressed in starved zebrafish myotubes

Abstract: The zebrafish (Danio rerio) remains the teleost fish of choice for biological investigations due to the vast array of molecular tools and resources available. To better understand the epigenetic regulation of autophagy, we utilized a primary myotube culture system generated from isolated myogenic precursor cells (MPCs) from zebrafish grown under starvation conditions using a media devoid of serum and amino acids. Here, we report starvation-induced regulation of several autophagy-related genes (atg) expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…We observed that nutrient deprivation induces an increase in expression of multiple autophagy-associated genes. This is in agreement with other studies, which analyzed the expression of a subset of proteins involved in autophagy under different starvation conditions, such as serum and amino acid deprivation [28] or glucose starvation [16]. Furthermore, we demonstrated that the expression of autophagy-associated genes was accompanied by an increase in POLR2 signal for these genes, validating that increased transcription contributes to the increased expression.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We observed that nutrient deprivation induces an increase in expression of multiple autophagy-associated genes. This is in agreement with other studies, which analyzed the expression of a subset of proteins involved in autophagy under different starvation conditions, such as serum and amino acid deprivation [28] or glucose starvation [16]. Furthermore, we demonstrated that the expression of autophagy-associated genes was accompanied by an increase in POLR2 signal for these genes, validating that increased transcription contributes to the increased expression.…”
Section: Discussionsupporting
confidence: 93%
“…This suggest that feedback at the transcriptional levels starts to become relevant after 6 h, or that these feedback loops are indirect, or that this is caused by differences between mice and men. Indeed, analysis of certain key autophagy genes in zebrafish has demonstrated that the increase in gene expression that is observed after 12 h of amino acid and serum starvation is absent after 24 h [28]. Additionally, our results indicate that the expression of autophagy-associated genes is not a measure of autophagic flux, because increased gene expression can still be observed in the absence of ATG7 and RB1CC1 , when no autophagic flux is present.…”
Section: Discussionmentioning
confidence: 72%
“…A recent study was conducted in zebrafish myotubes to identify histone modifications associated with autophagy promoters in normal versus starvation conditions. Under normal conditions, autophagy genes were marked by both activating (H3K4me3) and repressive (H3K9me3) modifications . Such domains, called bivalent domains, are present on developmentally important genes to balance their expression levels and poise these genes for activation upon stimuli .…”
Section: Epigenetic Control Of Autophagymentioning
confidence: 99%
“…In the early 2000s (24), a number of groups provided evidence of its important interactions with evolutionarily conserved amino terminal chromodomain of heterochromatin protein 1 (HP1), a hallmark of heterochromatin, thereby recruiting it to specific chromatin loci. To date, roles for H3K9me3 have been revealed in regulating apoptosis (25,26), autophagy (27), development (28,29), DNA repair (30)(31)(32)(33), splicing (34)(35)(36)(37)(38), self-renewal (39,40), transcriptional elongation (36), viral latency (41-43), imprinting (44), aging (45), and cell identity (46). In acute myeloid leukaemia (AML), alterations in H3K9 methylation at promoter regions were found to be associated with inactivation of tumour-suppressor genes and blockade of differentiation and deregulated proliferation (47,48).…”
Section: Discussionmentioning
confidence: 99%